Asteroids (Echinodermata) from the Crackers Member (lower Aptian, Deshayesites forbesi Zone) on the Isle of Wight (UK), with a revision of fossil Pseudarchasteridae. Issue 3 (August 2020) - Gale, Andy
Abstract: Asteroids from the lower Aptian Lower Greensand of the Isle of Wight are described. Two articulated specimens are referred to the extant paxillosid family Pseudarchasteridae and transferred to a living genus, i.e., Paragonaster, P. wightensis (Breton, 1992). Isolated marginal plates are assigned to the widespread Cretaceous astropectinid genus Coulonia, and described as C. caseyi sp. nov. The Cretaceous genus Comptonia Gray, 1840 is referred to the Pseudarchasteridae and revised taxonomically, with the recognition of two species; C. elegans Gray, 1840 and C. bretoni sp. nov., Paragonaster wightensis is the oldest known member of the Pseudarchasteridae.